IS THE CONCEPT OF WASTE UNIVERSAL? HANDLING BUILDING DEMOLITION BY-PRODUCTS IN THE CITY OF KANO, NIGERIA - Aminu Lawan ABDULLAHI; Angela LEE (Journal of Construction Project Management and Innovation)
While old and new studies such as the works of Henry Lewis Morgan in 1871 on kinship and Geert Hofstede in 1980 on management theories show that what works in one cultural setting may not work in another, the United Nation policies on environmental governance to-date tend to be a uniform approach for all nations irrespective of the differences in cultural orientation. This paper investigates and demonstrates that in the context of construction and demolition wastes, what may be considered as waste in one society may be a wealth in another society; and the waste management policies that work in one society may not work in another. Therefore the one-way traffic approach in international environmental governance whereby the waste management practices of the rich countries are considered as a perfect model to be emulated by the poorer countries may be wrong. In some instance, such as the building demolition management practices in Nigeria, the systems of the developing countries may even be more sustainable than what is obtainable in the rich countries. Instead of dismissing the systems of the developing countries as informal and inferior, such systems may be holding the key to the sustainable solutions for waste management that the world needs so much.